Pengembangan Bahan Ajar Digital dengan Pendekatan Collaborative Learning Menggunakan Padlet untuk Meningkatkan Writing Skills Siswa - Al-Fitrie, Ahmad Lazuardi; Solihatin, Etin; Kustandi, Cecep (Universitas Pendidikan Mandalika, 2023)
This research aims to analyze the feasibility and effectiveness of digital teaching materials with a collaborative learning approach using Padlet to improve students' ability to write explanatory texts. This research used research and development methods with a 4D model. The subjects of this research were Nida El-Adabi Islamic Middle School students in class VIII. Interviews, observations, and questionnaires were data collection instruments, then analyzed using percentage analysis techniques and the N-Gain effectiveness test. This research showed that the material test results obtained an average percentage of 90.9% (very feasible), and the media test results obtained 65.5% (feasible). In the assessment of one-to-one student trials, the score was 81.77%, while for small group trials, it was 88.02%. In the effectiveness test, it was found to be 81.55% (very feasible). The results of the initial writing ability assessment of the participants got a score of 75.83, and the results of the students' responses after the development got a score of 86.97. Developing digital teaching materials to improve writing skills using a collaborative learning approach using Padlet is very suitable for helping students improve their writing skills.